Deficiency in the amino aldehyde dehydrogenase encoded by GmAMADH2, the homologue of rice Os2AP, enhances 2-acetyl-1-pyrroline biosynthesis in soybeans (Glycine max L.) - Arikit, Siwaret; Yoshihashi, Tadashi; Wanchana, Samart; Uyen, Tran T.; Huong, Nguyen T. T.; Wongpornchai, Sugunya; Vanavichit, Apichart (Wiley, 2011)
2‐Acetyl‐1‐pyrroline (2AP), the volatile compound that provides the ‘popcorn‐like’ aroma in a large variety of cereal and food products, is widely found in nature. Deficiency in amino aldehyde dehydrogenase (AMADH) was previously shown to be the likely cause of 2AP biosynthesis in rice (Oryza sativa L.). In this study, the validity of this mechanism was investigated in soybeans (Glycine max L.). An assay of AMADH activity in soybeans revealed that the aromatic soybean, which contains 2AP, also lacked AMADH enzyme activity. Two genes, GmAMADH1 and GmAMADH2, which are homologous to the rice Os2AP gene that encodes AMADH, were characterized. The transcription level of GmAMADH2 was lower in aromatic varieties than in nonaromatic varieties, whereas the expression of GmAMADH1 did not differ. A double nucleotide (TT) deletion was found in exon 10 of GmAMADH2 in all aromatic varieties. This variation caused a frame‐shift mutation and a premature stop codon. Suppression of GmAMADH2 by introduction of a GmAMADH2‐RNAi construct into the calli of the two nonaromatic wild‐type varieties inhibited the synthesis of AMADH and induced the biosynthesis of 2AP. These results suggest that deficiency in the GmAMADH2 product, AMADH, plays a similar role in soybean as in rice, which is to promote 2AP biosynthesis. This phenomenon might be a conserved mechanism among plant species.